EFFECTIVENESS OF STRUCTURED ACTIVITY PROGRAMME ON COGNITIVE FUNCTION AMONG INMATES OF THE DESTITUTE HOME - G., Anjali K.; Nayak, Asha K.; Andrade, Maxie (Journal of Health and Allied Sciences NU, 2014)
Current trends in health care practice emphasis on cost effective consolidative approach of pharmacological and life style modification. This can help mentally challenged individual and destitute to obtain the optimum level of functioning. The study aimed to determine the effectiveness of structured activity programme on cognitive function, self-esteem and behaviour among mentally ill destitute home inmates. Study was conceptualized based on Albert Bandura's Triadic reciprocity of determinism. An evaluative approach using pre-test post-test design was used for the study. The samples were selected based on the sampling criteria and a total of 50 samples were recruited for the study with the mean age of 41.98±13.13. Study findings revealed that structured activity programme was effective in improving the cognitive function of mentally ill destitute. This suggests structured activities can be used in institutionalized or hospital setting to improve the cognition of mentally ill clients.
Keywords: Exercise programme; activity; cognitive function; mentally ill; destitute